Colorectal cancer screening: An update to the American Cancer Society guideline, 2026 - Andrew M. D. Wolf; Richard M. Hoffman; Louise C. Walter; Charnita Zeigler‐Johnson; Timothy R. Church; Carmen E. Guerra; Elena B. Elkin; Ruth Etzioni; Abbe Herzig; Kevin C. Oeffinger; Rebecca B. Perkins; Sana Raoof; et al. (CA: A Cancer Journal for Clinicians, 2026)
ABSTRACT Colorectal cancer (CRC) is a leading cause of cancer incidence and mortality in the United States, with rates recently increasing among adults younger than 65 years. In 2018, the American Cancer Society (ACS) lowered the recommended age to initiate screening for average‐risk adults to age 45 years. Since then, new molecular‐based screening tests—a multitarget stool RNA test (mt‐sRNA), a next‐generation mt‐sDNA test, and a blood‐based cell‐free DNA assay—have received regulatory approval for CRC screening. For this update, the ACS Guideline Development Group commissioned a targeted, systematic evidence review evaluating diagnostic performance and published modeling studies to judge the potential impact of these tests on CRC incidence and mortality. The ACS reaffirms the recommendation that average‐risk adults should initiate CRC screening at age 45 years and continue through age 75 years for those with a life expectancy greater than 10 years. Consistent with prior guidelines, the ACS emphasizes that offering multiple, recommended screening options supports informed patient choice and may improve participation, because the most effective screening test is the one that the patient completes. The next‐generation mt‐sDNA test, which is an updated version of an already recommended mt‐sDNA test, and the mt‐sRNA test demonstrated high sensitivity for CRC and moderate sensitivity for advanced precancerous lesions and are recommended, along with annual high‐sensitivity fecal immunochemical and high‐sensitivity guaiac‐based fecal occult blood tests, as preferred stool‐based screening options at 3‐year intervals. Compared with established stool‐based tests, blood‐based tests demonstrated lower sensitivity for both advanced precancerous lesions and stage I cancers, with modeling studies predicting less effectiveness in reducing CRC incidence and mortality. At this time, blood‐based tests should be recommended only to individuals who decline or do not complete preferred screening tests. Ongoing evaluation of adherence, real‐world implementation, and clinical outcomes will inform future updates for these new tests. For screening to be effective, a positive result on any noncolonoscopy screening test requires timely follow‐up with colonoscopy, preferably within 6 months, to complete the screening process.